1993
DOI: 10.1128/mcb.13.6.3311
|View full text |Cite
|
Sign up to set email alerts
|

Developmental analysis of tropomyosin gene expression in embryonic stem cells and mouse embryos.

Abstract: Tropomyosins (TMs) comprise a family of actin-binding proteins which play an important role in the regulation of contractility in muscle (cardiac, skeletal, and smooth) and nonmuscle cells. Although they are present in all cells, different isoforms are characteristic of specific cell types. In vertebrates, there are four different TM genes (a-TM, 1s-TM, TM30, and TM4), three of which generate alternatively spliced isoforms.This study defines the expression patterns of these isoforms during murine embryogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
87
2
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(99 citation statements)
references
References 53 publications
9
87
2
1
Order By: Relevance
“…We observed that S␣TM, a highly-specific protein marker of striated muscle cells and a very early marker of stem-cell cardiogenesis (15), was strongly induced by Shz small molecules in P19CL6 cells. Staining with the CH1 S␣TM-specific mAb identified large clusters of cardiac progenitor cells, found exclusively in Shz small-molecule-treated cultures (Fig.…”
Section: Activation Of Sarcomeric ␣-Tropomyosin Expression By Shz Smallmentioning
confidence: 80%
“…We observed that S␣TM, a highly-specific protein marker of striated muscle cells and a very early marker of stem-cell cardiogenesis (15), was strongly induced by Shz small molecules in P19CL6 cells. Staining with the CH1 S␣TM-specific mAb identified large clusters of cardiac progenitor cells, found exclusively in Shz small-molecule-treated cultures (Fig.…”
Section: Activation Of Sarcomeric ␣-Tropomyosin Expression By Shz Smallmentioning
confidence: 80%
“…Most recently, a developmental change of TM isoforms has been demonstrated using mouse embryonic stem cells and embryos; ␣-TM-SM mRNA is expressed in undifferentiated embryonic stem cells and in all stages of developing embryoid bodies, whereas the mRNA is detectable in postcoitum embryo (4.5 days) and increases during development, suggesting that expression of ␣-TM-SM occurs at very early developmental stages (54). However, these results are unclear with respect to localization of TM isoform mRNAs, because such study has been performed by RT-PCR using RNAs from whole embryoid bodies and embryos.…”
Section: Figmentioning
confidence: 99%
“…In contrast to bladder and aorta, the other tissues were more sensitive to the levels of transgene expression and could only support exon skipping at lower levels of expression. Expression of exon 2 containing ␣TM isoforms has been detected previously in murine ES cells at stages of embryonic development preceding the formation of SM tissues (25). However, that analysis did not look at the contemporaneous expression of exon 3-containing isoforms, so it is not clear whether the detected exon 2-containing ␣TM was a major or minor isoform.…”
Section: Figmentioning
confidence: 71%